2001
DOI: 10.1002/acp.741
|View full text |Cite
|
Sign up to set email alerts
|

Interviewing children and adults: the effect of question format on the tendency to speculate

Abstract: In formal interviews it is important that interviewees indicate when they do not know the answer, rather than speculate. In this study we investigated whether question format affected the tendency to speculate. One hundred and twenty-eight 5-to 9-year-olds, and 23 adults, were told two short stories, and were then asked questions about the stories. Half of the questions were answerable based on the information provided; the other half were not answerable. Within these categories, half of the questions were clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
134
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 31 publications
15
134
0
Order By: Relevance
“…In the current experiment, it is possible that adults did not guess more for closed than open questions because they were able to generate answers for the open questions. Indeed, adults have been shown to be less likely to guess answers to closed questions than children (Waterman, Blades, & Spencer, 2001). This difference in guessing may have contributed to the current results that suggested that adults were equally misled by certain types of closed and open questions.…”
Section: Discussionmentioning
confidence: 41%
“…In the current experiment, it is possible that adults did not guess more for closed than open questions because they were able to generate answers for the open questions. Indeed, adults have been shown to be less likely to guess answers to closed questions than children (Waterman, Blades, & Spencer, 2001). This difference in guessing may have contributed to the current results that suggested that adults were equally misled by certain types of closed and open questions.…”
Section: Discussionmentioning
confidence: 41%
“…Studies have amply demonstrated the benefits of questions that elicit multi-word responses, such as ''what,'' ''who,'' ''where,'' ''when,'' or ''how,'' in comparison to forced choice questions that limit responses to a single word, such as ''yes/no'' or multiple choice questions (e.g., Waterman, Blades, & Spencer, 2001). Open-ended questions elicit longer, more detailed, more accurate, and less self-contradictory responses from older children and adolescents than do the other types of interviewer utterances and are less likely to mislead younger children.…”
Section: Studies Of Child Interviewingmentioning
confidence: 99%
“…Children try to answer ''yes/no'' questions, even when the question is unanswerable; however, this is not the case for ''wh-'' questions (Waterman et al, 2001). Follow-up questions that require children to explain their reasoning, such as ''What makes you think so?''…”
mentioning
confidence: 99%
“…In an effort to reduce children's errors, researchers have examined the use of several forensically relevant conversational rules, including encouraging 'I don't know' responses (Mosten, 1990;Mulder & Vrij, 1996;Waterman, Blades, & Spencer, 2001), providing warnings about false suggestions (e.g. 'I may trick you, ' Warren, Hulse-Trotter, & Tubbs, 1991), and providing explanations concerning the interviewer's lack of knowledge (Mulder & Vrij, 1996).…”
Section: Reducing Memory Errors By Explaining Conversational Rulesmentioning
confidence: 99%
“…The results indicated that children who received either of the conversational rules made fewer errors than did children in the control group. Additionally, children who were given both rules made the fewest percentage of errors (but see Fritzley & Lee, 2003;Waterman et al, 2001;Waterman, Blades, & Spencer, 2000).…”
Section: Reducing Memory Errors By Explaining Conversational Rulesmentioning
confidence: 99%